PENGEMBANGAN SISTEM PENGEMASAN CERDAS BERBASIS NANOSENSOR: KUALITAS PANGAN DAN OBAT-OBATAN - Amanda Cahyani; Nabila Syifa Firdaus; Nor Latifah (Jurnal Riset Multidisiplin Edukasi, 2025)
Nanosensor-based smart packaging is a leading innovation in ensuring the quality and safety of food and drug products. This technology combines nanomaterials with advanced sensory systems to monitor the condition of products in real-time throughout the supply chain. The system allows for early detection of changes in temperature, humidity, pH, decay gases, and microorganisms, and provides accurate information on product quality. The nanosensors used have advantages in high sensitivity, selectivity, and stability. Despite facing technical challenges such as integration into packaging materials and production sustainability, the development of synthesis methods and fabrication technologies continues to overcome these constraints. The implementation of this smart packaging system has proven to be effective in extending shelf life, improving safety, and reducing product waste. Thus, nanosensors in smart packaging promise sustainable future solutions for the food and pharmaceutical industries.